Post-Earthquake Impact on Quality of Spring Water in Northern Pakistan - Aslam Mirza, M.; Khuhawar, M.Y.; Arain, R.; Aziz Choudhary, M.; Parveen Mahar, Khalida (Asian Journal of Chemistry, 2015)
This study was in progress before earth quake of October 8, 2005 and was extended to assay the post-earthquake impact on the spring water quality in highly devastated areas near the epicenter. The distressed area is situated at the foothills of Himalayas forming primarily the catchments area of Indus river. Thirteen springs were re-sampled 1 month after the earth quake in 2005. The preliminary results indicate TDS for half of the water samples within 115-499 mg/L, for the remaining half it exceeds 500 mg/L. Inter sample, seasonal and hydrological cycle variance indicate no significant change in elemental composition but those contaminated with sewage of deforested locations show substantial variation in elemental content. Low rainfall also deters the dilution of pollutants occurring both naturally and through human activity. This study provides the database of the quality of water of springs in the targeted area.